System-and-structural features of the phytobiotaof the fir-beech forests of the Pokuttia Carpathians - Myroslava Soroka; Andrzej Woźniak; Petro Plikhtiak; Anatoliy Goychuk; Ivanna Kulbanska (Наукові праці Лісівничої академії наук України)
The article presents the results of the system-structural analysis of the flora of fir-beech forests of the low mountain terrain of the Pokuttia Carpathians. A forest stand inventory, flora and mycobiota inventory, phytosociological descriptions of the vegetation and its syntaxonomic analysis were carried out. It was established that, in total, 223 species of higher vascular plants belonging to 168 genera, 65 families, 46 orders, 6 classes, 5 divisions, and 31 species of bryophytes from 30 genera, 24 families, 10 orders, 5 classes, 2 divisions were found in the composition of the vegetation cover of the fir-beech forests over an 11-year observation period. As was clarified, the coenoflora of fir-beech forests is arranged according to the scheme characteristic of broadleaved forests in general. It was found that among the life forms of plants in fir-beech forests, the leading role belongs to polycarpic herbs, the participation of which reaches 74.0%. Among perennial grasses in closed stands, long-rhizome species dominate (22.7%). When the phytoenvironment of fir-beech forests is changed in the process of selective felling, tap-rooted (19.3%) and bundle-rooted (11.3%) plants appear among herbaceous plants, the role of which in natural forests is insignificant. Among plants, vegetatively mobile species (40.0%) with a stress-tolerant life strategy (S) (55%) predominate. The fir-beech forests have a characteristic set of climomorphs – here there is a significant share of hemicryptophytes (46.0%) and cryptophytes (30.0%) and an insignificant participation of chamaephytes (3%). The set of ecological groups of plants in fir-beech forests is specific: sciomesophytes (30.1%), mesophytes (32.8%), megatrophs (22.4%), and neutrophils (34.6%) predominate here.